Epistemological Implications of Anthropological Field Work, with Notes from Northern Ontario - Hedican, Edward J. (Anthropologica, 2022)
This article engages in a critical discussion of the epistemological implications?how we know what we know issues?of the interpretive approach in recent social anthropology. Primary among these issues is the role of paradigms, or the lack of them as the postmodernists suggest, in anthropological field work and how these paradigms might be made to be more commensurate with one another. The problems of methodological verification and subjectivity—ethnography from whose point of view?—are related aspects of cross-cultural interpretation. The central point is that the main epistemological issues in anthropology are intrinsically tied to field work. Our field-work activity is the basis of all debate, it is at the centre of the interpretive endeavour and is the final arbiter about methodological issues. Some examples from the author's field work among the Ojibwa (Anishenabe First Nation) of northern Ontario are utilized to illustrate issues raised in the article.